2017
DOI: 10.3389/fnins.2017.00067
|View full text |Cite
|
Sign up to set email alerts
|

Fast Detector/First Responder: Interactions between the Superior Colliculus-Pulvinar Pathway and Stimuli Relevant to Primates

Abstract: Primates are distinguished from other mammals by their heavy reliance on the visual sense, which occurred as a result of natural selection continually favoring those individuals whose visual systems were more responsive to challenges in the natural world. Here we describe two independent but also interrelated visual systems, one cortical and the other subcortical, both of which have been modified and expanded in primates for different functions. Available evidence suggests that while the cortical visual system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 297 publications
(354 reference statements)
4
73
1
2
Order By: Relevance
“…Moreover, our results show that only the connection from the pulvinar to the amygdala is specifically related to fearful face processing. This suggests a central role for the pulvinar in processing emotional faces, as has been found by previous studies in the macaque 11,39 . We did not exhaustively explore the extent to which the cortex contributes information to the pulvinar-amygdala connection.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is Thesupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, our results show that only the connection from the pulvinar to the amygdala is specifically related to fearful face processing. This suggests a central role for the pulvinar in processing emotional faces, as has been found by previous studies in the macaque 11,39 . We did not exhaustively explore the extent to which the cortex contributes information to the pulvinar-amygdala connection.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is Thesupporting
confidence: 86%
“…These studies have consistently found evidence for a forward connection between the pulvinar and amygdala [8][9][10] . The dynamic causal relationship between the superior colliculus and the pulvinar, however, remains unexplored in the human brain 11 . The pulvinar also has several functional and cytoarchitectural subregions 12 and it is unclear how these connect to the superior colliculus and the amygdala and what roles these subregions may play in mediating transmission along the subcortical route 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although the pulvinar is commonly considered a single thalamic nucleus, it contains a number of distinct subregions which may be differentially involved in the various functions ascribed to the pulvinar (e.g. visual attention, decision making, motor planning, perceptual suppression, synchronization of cortical activity, detection of faces or fearful stimuli; Dominguez-Vargas et al, 2017; Grimaldi et al, 2016; Van Le et al, 2014; Le et al, 2014, 2016; McFadyen et al, 2017; Soares et al, 2017; Wilke et al, 2009, 2010, 2013; Zhou et al, 2016). In order to understand how the pulvinar contributes to these various tasks, the synaptic circuits within each subregion must first be defined.…”
mentioning
confidence: 99%
“…In fact, social cues provided by the human face differ strikingly depending on the emotion expressed (even among negative emotions). For example, angry faces usually signal imminent aggression, while fearful faces are related to potential threat in the environment [45]. Another possible explanation for the inconsistent findings may be that the paradigms vary significantly across studies.…”
Section: Behavioural Correlates Of Facial Emotion Processingmentioning
confidence: 78%